PENGENDALIAN KUALITAS MENGGUNAKAN METODE FMEA (FAILURE MODE AND EFFECT ANALYSIS) DI PT. ASIA MANDIRI LINES SURABAYA - Jonathan Elbert; Antonius Budhiman Setyawan; Stefanus Budy Widjaja S. (CALYPTRA, 2018)
This report aims to describe a quality control by using FMEA (Failure Mode and Effect Analysis) method to identify and prevent errors that arise in the process of delivery of goods in PT. Asia Mandiri Lines. FMEA (Failure Mode and Effect Analysis) is used as a guide for quality control in the company. Activities that are often done during field work practice is making a receipt letter for customers who want to send goods through PT. Asia Mandiri Lines. During the practical work in the administrative section, especially the handling of the mail and receipt of goods, found some problems that cause complaints from customers. It shows that the quality of freight service in PT. Asia Mandiri Lines should be fixed. Therefore, based on the results of the discussion of Field Work Report, I use FMEA (Failure Mode and Effect Analysis) method to help PT. Asia Mandiri Lines in reducing e rors, providing solutions for errors that occur, and improve the quality of the company in the process of delivery of goods.